2022
DOI: 10.1002/agt2.161
|View full text |Cite
|
Sign up to set email alerts
|

Modulating the aggregation of amyloid proteins by macrocycles

Abstract: The aggregation of amyloid proteins has been suggested to be the main cause of multiple human disorders; for example, amyloid β aggregates in Alzheimer's disease and α-synuclein aggregates in Parkinson's disease. In the search for therapeutic medicines, many molecules have been discovered and developed to modulate the aggregation of amyloid proteins. This century has witnessed the flourishing growth of supramolecular chemistry, and some biocompatible macrocycles have been proven to inhibit the aggregation of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 109 publications
1
12
0
Order By: Relevance
“…1B), the intensity ratio of CL to the emission of the tryptophan residue for the solid-state HEWL was bigger, suggesting the CTE effect. 26…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…1B), the intensity ratio of CL to the emission of the tryptophan residue for the solid-state HEWL was bigger, suggesting the CTE effect. 26…”
Section: Resultssupporting
confidence: 77%
“…1B), the intensity ratio of CL to the emission of the tryptophan residue for the solid-state HEWL was bigger, suggesting the CTE effect. 26 BSA is another protein that we tested. It has a molecular weight of 66 kDa and contained 583 amino acids with 8.4% aromatic amino acids, including phenylalanine (4.7%), tyrosine (3.4%) and tryptophan (0.3%).…”
Section: Of Proteinsmentioning
confidence: 99%
“…A key pathological hallmark of neurodegenerative diseases is the abnormal accumulation of amyloid aggregates in cells, which leads to neuronal malfunction and cell death. It was reported that liquid–liquid phase separation (LLPS) is closely regarded as an initial stage of amyloid aggregation, such as Tau in Alzheimer’s disease (AD), TAR DNA-binding protein 43 (TDP-43), and FUS protein in amyotrophic lateral sclerosis (ALS) and frontotemporal lobar degeneration (FTLD).…”
mentioning
confidence: 99%
“…Protein aggregation is a multistep process that is associated with a growing number of human diseases, including neurodegenerative disorders, metabolic disorders, and cancers. Solvatochromic probes have been developed to reveal protein misfolding in both test tubes and living cells, as represented by Prodan, SBD, and others. In recent years, AIEgens have been applied to detect protein unfolding, oligomerization, and aggregation. 1,2-Bis­[4-(3-sulfonatopropoxyl)­phenyl]-1,2-dipheny-lethene salt (BSPOTPE), a biocompatible AIEgen, was used to report insulin amyloid genesis . BSPOTPE exhibits significant fluorescence activation that correlates with insulin nucleation, elongation, and equilibrium phases, thus enabling the assessment of the amyloid genesis kinetics.…”
Section: Follow the Breadcrumbs: Detection And Monitoringmentioning
confidence: 99%